CA2+ INTRASELULER TERLIBAT DALAM MEKANISME PEMBUKAAN STOMATA AKIBAT PENGARUH AUXIN - PHARMAWATI, MADE; DEFIANI, MADE RIA; ARPIWI, Ni LUH (Jurnal Biologi Udayana; Vol 12 No 1 (2008): JURNAL BIOLOGI, 2008)
Research was done to elucidate the role of Ca2+ intracellular in stomatal movement induced by auxin. Two types of auxin (IAA and NAA) increased stomatal opening and the increase was concentration dependent. The addition of EGTA, Ruthenium red and Procaine as the modulator of Ca2+ concentration , inhibited stomatal opening induced by auxin. EGTA and procaine significantly inhibited somatal opening at 100 uM and 1 mM. Ruthenium red worked at lower concentrations which were 10 uM, 50 uM and 100 uM on LAA-induced stomatal opening, while on NAA-induced stomatal opening, Ruthenium red had an effect at 10 uM, 50 uM, 100 uM dan 1 mM. It is suggested that Ca2+ involves in stomatal opening induced by LAA and NAA as signaling agent.
Keywords: calcium; auxin; stomata